TRANSFORMASI KEMAMPUAN NUMERASI SISWA SMP SELAMA PELAKSANAAN ASESMEN KOMPETENSI MINIMUM PROGRAM KAMPUS MENGAJAR ANGKATAN 4 - Sulisawati, Dwi Noviani; Putri , Reta Eksa (Universitas Insan Budi Utomo, 2023)
The purpose of this study was to analyze the transformation of Asesmen Kompetensi Minimum values ​​related to students' numerical abilities which were carried out at SMP Islam Terpadu Syarif Hidayatullah Sukorambi. This study used a qualitative descriptive method, where the research subjects were class VIII students, totaling 15 students. Data collection was carried out twice, namely pre-test and post-test during the Kampus Mengajar Program batch 4. Each question consisted of 20 items with 12 indicators. The highest increasing scores of the two are in indicators number 2, 5, and 9. Balanced or equal scores are found in indicators number 1, 4, 6, 7, and 8. There is a decrease in scores in indicators number 3 and 12. These results indicate that there is a significant transformation marked by an increase in score from the pre-test average of 19.42% to the post-test average of 28.33%. Both are in the range of values ​​≤40. From this, it can be concluded that the numeracy skills SMP Islam Terpadu Syarif Hidayatullah students belong to the low category so improvements are needed in improving numeracy skills accompanied by support from the school.